[István Peterdi 4]
Zeppelin, children in the park, sailing-boat, family, holiday to Munich with car through the Alps, Maria-Zell, Bad Ischl, Salzburg, Munich, Zugspitze, soldiers marching, large guns, short film about parachutists, 1934 Zell am See, waterfall, girls dancing playing, skating, family holiday in the mountains, shooting in the air, procession, church, girl's first communion, walk in the mountains, Venice